Batch and continuous flow treatment studies of trichloroethylene contaminated in water by silver and cerium doped zinc oxide adsorption and photocatalysis - Sarttrawut Tulaphol; Nurak Grisdanurak; Anariba, Franklin; Chantra Tongcumpou; Pummarin Khamdahsag (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of photocatalytic treatment in continuous flow systems to be more practical is challenging. This research aimed to study batch and continuous flow treatment of trichloroethylene (TCE) contaminated in water by silver and cerium doped zinc oxide (0.005Ag-0.005Ce-ZnO) visible light driven photocatalyst. This catalyst was selected to represent the green route synthesis with simplicity and ease of upscaling. The 0.005Ag-0.005Ce-ZnO powder was synthesized using sticky rice flour as a template. Mechanical coating of the 0.005Ag-0.005Ce-ZnO powder on activated alumina (Al2 O3 ) beads was done to improve the appropriate packing in the fixed bed columns. Characterization of 0.005Ag-0.005Ce-ZnO showed a higher response to visible light and smaller crystallite size compared to zinc oxide synthesized with the same method. Using sticky rice starch as a template increased the uniform distribution of the elements. The photocatalytic batch test over 0.005Ag-0.005Ce-ZnO powder, 0.30 g/100 mL, could remove TCE up to 80% in 180 min. The decrease of TCE via photocatalysis compared to volatilization, adsorption, and photolysis presented the predominance of photocatalysis. Langmuir-Hinshelwood kinetics described that the decrease of TCE more depended on the reaction than adsorption. In addition, the TCE degradation steadily remained at 80-90% along the run of 0.005Ag-0.005Ce-ZnO@Al2 O3 photocatalysis under visible light from both warm white lamps and sunlight in the continuous flow system. Besides photocatalysis, TCE adsorption on 0.005Ag-0.005CeZnO@Al2 O3 packed in the columns showed significant results. Our findings presented the possibility of applying the photocatalytic continuous flow system to remove TCE in industrial wastewater.